Using Of Multimedia Technologies In Teaching Foreign Language - et. al., Aziza Fayzullaeva, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Following work is dedicated to the process of learning a foreign language is a complex, constantly evolving system. Computerization of foreign language teaching helps to facilitate access to information and reduce the time of language learning. This is mainly due to the fact that when using the Internet as one of the means of teaching a foreign language, many goals and objectives of the learning process are better realized.